Application of the multi-configuration Hartree-Fock theory to a simple model - Abecasis, Sara Mabel (1969)
The Lipkin model is extended to yield a non-trivial Hartree-Fock (HF) solution for any coupling constant of the two-body force. In this model the multi-configuration Hartree-Fock (MCHF) approach is compared with the exact solution and with the HF solution. The results show a strong superiority of the MCHF method over the HF approximation.